Feed Utilization and Growth Performance Responses to Incremental Dietary Levels of Tomato Pomace Powder in Finishing Sheep (Research in Agriculture Livestock and Fisheries, 2025)
Agro-processing by-products such as tomato pomace (TP) contain high levels of protein, fat and bioactive compounds such as phenolics, lycopene, and beta-carotene. Accordingly, the inclusion of TP in lamb diets has the potential to improve the feed utilization, and growth performance in finishing lambs. This study was, therefore, designed to investigate the maximum tolerance level of TP in finishing lambs using nutrient utilization and growth performance as indicators. A feeding trial was conducted using 35, five months old ram lambs (22.8 ± 5.6 kg) to evaluate changes in feed intake, weight gain, and feed conversion ratio (FCR) in response to incremental levels of TP. The lambs were randomly assigned to five diets which were formulated including milled tomato pomace in the conventional lamb finisher diet at 0 (TP0), 15 (TP15), 30 (TP30), 45 (TP45), and 60% (TP60) on a dry matter basis. Overall, TP45 had the highest (679.36 kg) total feed intake while TP60 had the least (510.22 kg) total feed intake. Tomato pomace inclusion had a significant effect (P < 0.05) on weight gain in weeks 1 – 4 but not (P > 0.05) in weeks 5 – 9. Lambs fed TP containing diets had the highest overall weight gain (OWG) and a lower overall FCR when compared to the control diet (TP0). Based on the improved weight gain, feed intake and FCR, it was concluded that TP inclusion in lamb diets enhances feed utilization and growth performance of lambs and the optimum TP inclusion is 33%.Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 353-365